2015
DOI: 10.4236/ajps.2015.619297
|View full text |Cite
|
Sign up to set email alerts
|

Micronutrient Status in Soil of Central India

Abstract: Two major issues, i.e. large crop productions and huge anthropogenic activities (e.g. fuel burning and mineral roasting) disturb the micronutrient balance in the soil of India. In this work, the available and total status of eight micronutrients i.e. Fe, Mn, Cu, Zn, Co, Ni, Mo, and S of the soils in the most urbanized area: Raipur area, Chhattisgarh, India (extending over ≈ 2 × 10 4 km 2) is described. The available status of micronutrients i.e. Fe, Mn, Cu, Zn, Co, Ni, Mo and 2 4 SO − in the soils (n = 100) wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 12 publications
3
18
2
Order By: Relevance
“…The wide variation in concentration of nutrients in the study area is ascribed to different parent materials, prevailing climatic conditions, and natural and anthropogenic activities. Our findings are in line with the results reported by Patel et al (2015) who recorded the available status of micronutrients, that is, Fe, Zn, Mo and S in the soils of central India, which ranged at 30-8,253, 0·7-5·0, 0·1-8·9 and 41-747 mg kg À1 with mean value of 642 AE 186, 2·3 AE 0·2, 1·5 AE 0·3 and 281 AE 25 mg kg À1 , respectively. Shukla et al (2016) also reported mean values of 1·66, 1·37, 10·30 and 12·20 mg kg À1 for available Zn, Cu, Mn and Fe, respectively, in soils of intensively cultivated Trans-Gangetic Plains of India.…”
Section: Descriptive Statisticssupporting
confidence: 92%
See 1 more Smart Citation
“…The wide variation in concentration of nutrients in the study area is ascribed to different parent materials, prevailing climatic conditions, and natural and anthropogenic activities. Our findings are in line with the results reported by Patel et al (2015) who recorded the available status of micronutrients, that is, Fe, Zn, Mo and S in the soils of central India, which ranged at 30-8,253, 0·7-5·0, 0·1-8·9 and 41-747 mg kg À1 with mean value of 642 AE 186, 2·3 AE 0·2, 1·5 AE 0·3 and 281 AE 25 mg kg À1 , respectively. Shukla et al (2016) also reported mean values of 1·66, 1·37, 10·30 and 12·20 mg kg À1 for available Zn, Cu, Mn and Fe, respectively, in soils of intensively cultivated Trans-Gangetic Plains of India.…”
Section: Descriptive Statisticssupporting
confidence: 92%
“…Our findings are in line with the results reported by Patel et al . () who recorded the available status of micronutrients, that is, Fe, Zn, Mo and S in the soils of central India, which ranged at 30–8,253, 0·7–5·0, 0·1–8·9 and 41–747 mg kg −1 with mean value of 642 ± 186, 2·3 ± 0·2, 1·5 ± 0·3 and 281 ± 25 mg kg −1 , respectively. Shukla et al .…”
Section: Resultsmentioning
confidence: 99%
“…EC, K, and Fe were positively correlated whereas correlation was negative with Mn at P = 0.01. The correlation between EC, Zn, and Cu at these levels were not significant (Patel et al, ). Corwin and Lesch () opined that soil EC is an indirect indicator of salinity levels and nutrient availability in soils.…”
Section: Resultsmentioning
confidence: 99%
“…This indicated wide spread deficiency of Zn, Cu, and Fe (Figure g–j). The micronutrient contents were found several folds lesser than in central India and Trans‐gangetic plains (Patel et al, ). High variability existed for micronutrients with CV ranging from 65.0 to 121.…”
Section: Resultsmentioning
confidence: 99%
“…Micronutrients play a vital role in crop growth, crop productivity, soil fertility and human nutrition (Patel et al, 2015). Arnon and Stout (1939) proposed that, Cu is an essential element for plant growth.…”
Section: Introductionmentioning
confidence: 99%